Offshore mechatronics systems engineering - Karimi, Hamid Reza (CRC Press, Taylor & Francis Group, 2018)
The book gives a systematical and almost self-contained description of the many facets of envisaging, designing, implementing or experimentally exploring offshore mechatronics and systems along the adequate designs of integrated modeling, safety, control and supervision infrastructure. It will serve as a reference for graduate and postgraduate students and for researchers in all engineering disciplines, including mechanical engineering, electrical engineering and applied mathematics to explore the state-of-theart techniques for solving problems of integrated modeling, control and supervision of complex offshore plants with collective safety and robustness.